Interculturality and science teaching: A classroom daily routine - Juarez Melgaço Valadares; Célio Silveira Júnior (Education Policy Analysis Archives, 2020)
Historically, science has become an obstacle to the introduction of other kinds of knowledge in schools. Since 1990, the superiority of scientific knowledge has been criticized by education researchers. In parallel, indigenous education has been proving itself as a privileged space of recognition of relationships among cultural groups, in a way that traditional types of knowledge have been incorporated into the school curriculum, bringing other challenges to the pedagogical work. In this paper, we discuss a case study in which traditional types of knowledge were part of a course from the Undergraduate Program for Indigenous Educators at Federal University of Minas Gerais. We collected interrelated situations involving food planting and astronomical observations under various conceptions, and we developed them in a dialogic form in the classroom. The strengthening of indigenous cultures was rethought as the interlocution kept made us see the viability of the cultural dialogue in its complexity. We hope to contribute to overcome the dichotomy between scientific knowledge and traditional culture in the curricular propositions of indigenous and non-indigenous school education.